2010
DOI: 10.3390/molecules15064467
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of European Cranberrybush Fruit (Viburnum opulus var. edule)

Abstract: In the literature there is little available information concerning European cranberrybush fruit (Viburnum opulus var. edule). This plant can be cultivated, even in harsh climatic conditions, because of its low environmental demands, and it is possible to harvest the fruit even in the snow cover. The aim of this study was to determine the content of polyphenolics, antioxidant activity, flavonoids and vitamin C in the fruit of three cultivars ´Leningradskaya otbornaya´, ´Souzga´ and ´Taezny rubiny´ of this speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 34 publications
3
55
1
4
Order By: Relevance
“…It seems that the genotype strongly influences the accumulation of flavonoids in European Cranberrybushes. Rop et al (2010) determined the total flavonoid content in fresh fruits of V. opulus to be 314-489 mg per 100 g, indicating higher values than in our study. Flavonoid compounds with antioxidant properties reduce inflammation, form healthy blood vessels, prevent cell damage and delay ageing (Kahraman et al 2002).…”
Section: Bioactive Contentcontrasting
confidence: 49%
“…It seems that the genotype strongly influences the accumulation of flavonoids in European Cranberrybushes. Rop et al (2010) determined the total flavonoid content in fresh fruits of V. opulus to be 314-489 mg per 100 g, indicating higher values than in our study. Flavonoid compounds with antioxidant properties reduce inflammation, form healthy blood vessels, prevent cell damage and delay ageing (Kahraman et al 2002).…”
Section: Bioactive Contentcontrasting
confidence: 49%
“…In several studies, chlorogenic acid has been reported as the main phenolic compound in Viburnum species (Altun & Yilmaz, 2007;Kraujalyte, Venskutonis, Pukalskas, & Cesoniene, 2013;Çam & Hisil, 2007). V. opulus fruit contains high amounts of polyphenolics (Rop et al, 2010), phenolic acids (Velioglu et al, 2006), flavonoids and anthocyanins (Cesoniene, Daubaras, Viškelis, & Šarkinas, 2012;Velioglu et al, 2006) as well as organic acids, including ascorbic (Rop et al, 2010) and L-malic acids (Çam & Hisil, 2007). On-line HPLC-DPPH method has been utilised to study antioxidant composition of the fruits of some Viburnum species (Kraujalyte et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…in folklore medicine, the traditional beverage "gilaburu" prepared from the fruits has been used for the treatment of gallbladder, liver diseases and diabetes in the central Anatolia region of turkey (2,7). Antioxidant (2,50,52), anticancer (34), antibacterial (34,52,62), antinociceptive and anti-inflammatory (1) activities of V. opulus have been reported. Yilmaz et al (63) reported the antinociceptive and anti-inflammatory activity of V. lantana leaves.…”
Section: Introductionmentioning
confidence: 99%